Sleep medications and alcohol abuse masked sleep apnea syndrome without sleepiness for over 30 years: A case report - Naoya Onishi; Keiichiro Nishida; Hironari Minami; Katsunori Toyoda; Yoshitaka Nishizawa; Yoichiro Kubo; Soichiro Ikeda; Tetsufumi Kanazawa (PCN Reports)
Abstract Background Insomnia is often treated with benzodiazepines, which can lead to long‐term use and potential complications, especially if underlying conditions like sleep apnea syndrome (SAS) go undiagnosed. This case report describes a 70‐year‐old woman with chronic insomnia, benzodiazepine and alcohol abuse, and a previously undiagnosed severe SAS. Case Presentation The patient, a 70‐year‐old woman was admitted for suspected delirium caused by benzodiazepine and alcohol abuse. She had been prescribed benzodiazepines by multiple health care providers for over 30 years. Additionally, she regularly consumed alcohol to self‐medicate. These were replaced and treated with diazepam, but her sleep disturbances persisted. She had a noticeable snoring during her hospitalization, which led to a polysomnography. The results revealed that she had severe SAS with an apnea–hypopnea index of 57.1 during total sleep time. Continuous positive airway pressure therapy significantly improved her sleep quality. She also underwent testing for dementia, which showed frontal lobe dysfunction on imaging and psychological testing. She was discharged after 66 days of treatment, able to live independently with home care support. Conclusion This oversight led to prolonged use of benzodiazepines and self‐medication with alcohol, worsening her condition. The case emphasizes the need for thorough assessments in patients with treatment‐resistant insomnia, particularly to identify organic causes like SAS that may be contributing to their symptoms. This case highlights the importance of reevaluating patients whose insomnia does not improve with sleep medication.